2013
DOI: 10.1051/0004-6361/201321084
|View full text |Cite
|
Sign up to set email alerts
|

Refined physical properties andg′,r′,i′,z′,J, H, Ktransmission spectrum of WASP-23b from the ground

Abstract: Context. Multi-band observations of planetary transits using the telescope defocus technique may yield high-quality light curves suitable for refining the physical properties of exoplanets even with small or medium size telescopes. Such observations can be used to construct a broad-band transmission spectrum of transiting planets and search for the presence of strong absorbers. Aims. We have thoroughly characterised the orbital ephemeris and physical properties of the transiting planet and host star in the WAS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 55 publications
(92 reference statements)
2
29
0
Order By: Relevance
“…Due to the relatively long STIS integration time (i.e. 287 s), the data contains large number of cosmic ray events, which were identified and removed following the procedures described in Nikolov et al (2013). It was found that the total number of pixels affected by cosmic ray events comprise ∼ 4 % of the total number of pixels of each 2D spectrum.…”
Section: Hst Stis Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the relatively long STIS integration time (i.e. 287 s), the data contains large number of cosmic ray events, which were identified and removed following the procedures described in Nikolov et al (2013). It was found that the total number of pixels affected by cosmic ray events comprise ∼ 4 % of the total number of pixels of each 2D spectrum.…”
Section: Hst Stis Spectroscopymentioning
confidence: 99%
“…clear/hazy/cloudy, delve into the presence/lack of TiO/alkali and other molecular features, probe the diversities between possible subclasses and perform comparative exoplanetology. Initial results from four exoplanets have been presented so far in Huitson et al (2013) for WASP-19b, Wakeford et al (2013) and Nikolov et al (2013) for HAT-P-1b and Sing et al (2013) for WASP-12b and Sing et al (2014) for WASP-31b. Already a wide diversity among exoplanet atmospheres is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous multiband observations of planetary transits have been obtained for several TEP systems using the instruments BUSCA (Southworth et al 2012b;Mancini et al 2013c), GROND (de Mooij et al 2012;Bayliss et al 2013;Mancini et al 2013a,b;Mohler-Fischer et al 2013;Nikolov et al 2013;Penev et al 2013;Southworth et al 2013), ULTRACAM (Bento et al 2013;Copperwheat et al 2013) and SIRIUS (Narita et al 2013). Table 1.…”
Section: Multiband Observations Of Planetary Transitsmentioning
confidence: 99%
“…Southworth et al 2012b;Copperwheat et al 2013;Nikolov et al 2013;Mancini et al 2013c;Narita et al 2013;Chen et al 2014). We used our multi-band data to investigate possible variations of the radius of HAT-P-23 b and WASP-48 b in different optical passbands.…”
Section: Figmentioning
confidence: 99%